Anxiety Description of Social Workers in Assisting Children in Conflict with the Law - Muhammad Ilham; Desmita Desmita; Abdel Monef; Hizrati Hizrati (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2022)
This study aims to determine the anxiety of social workers and determine the type of anxiety in social workers in assisting ABH. This type of research is descriptive qualitative research. The results of the author's study found that: 1) the description of anxiety in social workers in assisting children in dealing with the Law found that one social worker in the social service office in fifty cities with the initials AA had three aspects of anxiety, namely behavioral aspects, cognitive aspects, and magical aspects. On the other hand, social workers with the initial Y only have one part of stress: behavioral. Furthermore, 2) the type or form of anxiety for social workers in assisting children in dealing with the Law, it was found that one social worker at the social service office in fifty cities had a type of social worker anxiety with the initial Y having mild anxiety.